(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
Background. The study analyses sport as the basic contents of leisure in biodromal perspective ad the ascetic lifestyle of an athlete. Ascetic lifestyle is observed not only as it contributes to the best performances, but also to lifelong participation including, for instance, long-distance runners with the stage of minimally 20 years of competition racing. The latter is the centre of our attention. The object of the research is sport as the basic contents of leisure in biodromal perspective. Research aim is to analyse the ascetic lifestyle of an athlete; to map the real role of asceticism in the sports sphere on example of long-distance runners. Methods. We researched a special group of long-distance runners with the stage of minimally 20 years of competition racing (168 athletes). A research questionnaire with this special group was implemented. Descriptive statistical evaluation was performed. Results. We found noticeable ascetic features of lifestyle among long-distance runners with the stage of minimally 20 years of competition racing. They exercise (it is an original meaning of the Greek word askésis) both body and will in lifelong horizon. They know that running (which is higher level of jogging) is also joined with some portion of pain and they are ready to sign a specific runners´ motto: “Pain is inevitable. Suffering is optional.” If the option is “suffering”, the situations open the way to peak experiences. Conclusion. Promoting “reasonable asceticism” can be one aspect of raison d´être of today’s sport in this postmodern world with the supremacy of hedonistic orientation. Keywords: leisure, running, lifestyle, motivation, asceticism.